Arc-Evaporated Nanoscale Multilayer Nitride-Based Coatings for Protection Against Wear, Corrosion, and Oxidation - Pogrebnjak, A.D.; Ivasishin, O.M.; Beresnev, V.M. (Успехи физики металлов, 2016)
The studies of the structure and properties of nanoscale multilayer coatings based on the nitrides of refractory metals are summarized in a brief review. By the example of TiN/MoN, TiN/ZrN, CrN/MoN, and more complex (multilayer) (TiZrNbTaHf)N/WN:(TiZrNbTaHf)N/MoN obtained by vacuum-arc deposi-tion of cathode, the dependences of their hardness, wear resistance, friction, corrosion, and oxidation on conditions of the deposition and layers’ thickness are investigated and analysed. The regularities of the structure and behaviour properties of such nanoscale multilayer coatings depending on the size of nanograins, textures, and stresses arising in these coatings are described. В кратком обзоре обобщены результаты исследований структуры и свойств наномасштабных многослойных покрытий нитридов тугоплавких металлов. На примере TiN/MoN-, TiN/ZrN-, CrN/MoN- и более сложных (многослойных) (TiZrNbTaHf)N/WN:(TiZrNbTaHf)N/MoN-покрытий, полученных методом вакуумно-дугового осаждения катода, исследованы и проанализированы зависимости их твёрдости, износостойкости, трения, коррозии и окисления от условий осаждения и толщины слоёв. Отмечены закономерности структуры и свойств поведения таких наномасштабных многослойных покрытий от размера нанозёрен, текстуры и напряжений, возникающих в этих покрытиях. У короткому огляді узагальнено результати досліджень структури та влас-тивостей наномасштабних багатошарових покриттів нітридів тяжкотоп-ких металів. На прикладі TiN/MoN-, TiN/ZrN-, CrN/MoN- та більш склад-них (багатошарових) (TiZrNbTaHf)N/WN:(TiZrNbTaHf)N/MoN-покриттів, одержаних методою вакуумно-дугового осадження катоду, досліджено та проаналізовано залежності їх твердости, зносостійкости, тертя, корозії й окиснення від умов осадження та товщини шарів. Відмічено закономірнос-ті структури та властивостей поведінки даних наномасштабних багатоша-рових покриттів від розміру нанозерен, текстури та напруг, що виникають у цих покриттях.